A New Robotic Endoscope Holder for Ear and Sinus Surgery with an Integrated Safety Device - Guillaume Michel; Philippe Bordure; Damien Chablat (Sensors, 2022)
In the field of sinus and ear surgery, and more generally in microsurgery, the surgeon is faced with several challenges. The operations are traditionally carried out under binocular loupes, which allows for the surgeon to use both hands for a microinstrument and an aspiration tool. More recently, the development of endoscopic otological surgery allowed for seeing areas that are difficult to access. However, the need to handle the endoscope reduces the surgeon’s ability to use only one instrument at a time. Thus, despite anaesthesia, patient motions during surgery can be very risky and are not that rare. Because the insertion zone in the middle ear or in the sinus cavity is very small, the mobility of the endoscope is limited to a rotation around a virtual point and a translation for the insertion of the camera. A mechanism with remote center motion (RCM) is a good candidate to achieve this movement and allow for the surgeon to access the ear or sinus. Since only the translational motion along the main insertion axis is enabled, the ejection motion along the same axis is safe for the patient. A specific mechanism allows for inserting and ejecting the endoscope. In a sense, the position is controlled, and the velocity is limited. In the opposite sense, the energy stored in the spring allows for very quick ejection if the patient moves. A prototype robot is presented using these new concepts. Commercially available components are used to enable initial tests to be carried out on synthetic bones to validate the mobility of the robot and its safety functions.